Making it to the top in team sports: Start later, intensify, and be determined! - Moesch, K.; Trier Hauge, M. L.; Wikman, J. M.; Elbe, A.-M. (Talent Development & Excellence, 2013)
Young athletes need to specialize early, or if it is more beneficial to follow the path of early diversification. The present study investigates the career paths and related motivational and volitional factors of Danish elite and near - elite team sport athletes. Seventy - six athletes matched by sport, age and sex participated in the study. Elite athletes started their career later and showed higher self-determination and lower values in postponing training. The logistic regression showed that fewer accumulated training hours up to age 12, but more up to age 15 significantly predicted elite group membership. All other investigated variables did not show significant results. It is concluded that there are more similarities than differences between the two groups.